2017
DOI: 10.5964/jnc.v3i2.62
|View full text |Cite
|
Sign up to set email alerts
|

A role for attentional reorienting during approximate multiplication and division

Abstract: When asked to estimate the outcome of arithmetic problems, participants overestimate for addition problems and underestimate for subtraction problems, both in symbolic and non-symbolic format. This bias is referred to as operational momentum effect (OM). The attentional shifts account holds that during computation of the outcome participants are propelled too far along a spatial number representation. OM was observed in non-symbolic multiplication and division while being absent in symbolic multiplication and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
(74 reference statements)
2
6
0
Order By: Relevance
“…At the very least, the results in the present study showed that the interaction between space and multiplication (or division) operation was – if it exists at all – weaker than those for addition and subtraction operations. These results also support the findings of Katz et al (2017) who found that the cognitive processes underlying multiplication and division are less prone to spatial biases compared to addition and subtraction. Therefore, the dissociation in our current study suggested that the cognitive mechanisms underlying multiplication and division operations might be different from those for addition and subtraction ( Katz et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…At the very least, the results in the present study showed that the interaction between space and multiplication (or division) operation was – if it exists at all – weaker than those for addition and subtraction operations. These results also support the findings of Katz et al (2017) who found that the cognitive processes underlying multiplication and division are less prone to spatial biases compared to addition and subtraction. Therefore, the dissociation in our current study suggested that the cognitive mechanisms underlying multiplication and division operations might be different from those for addition and subtraction ( Katz et al, 2017 ).…”
Section: Discussionsupporting
confidence: 90%
“…These results also support the findings of Katz et al (2017) who found that the cognitive processes underlying multiplication and division are less prone to spatial biases compared to addition and subtraction. Therefore, the dissociation in our current study suggested that the cognitive mechanisms underlying multiplication and division operations might be different from those for addition and subtraction ( Katz et al, 2017 ). However, the Bayes factor analysis indicated that more data are needed to make this conclusive in future work.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additions and subtractions have been thought to involve shifts of attention along a mental number line: a shift of attention toward the right (or toward larger numbers) for addition and toward the left (smaller numbers) for subtraction (Knops et al, 2009a,b;Masson and Pesenti, 2014;McCrink et al, 2007;Pinhas and Fischer, 2008). Importantly, these shifts of attention have not been reported for multiplication and division operations (Katz and Knops, 2014;Katz et al, 2017, Li et al, 2018Mathieu et al, 2016). In accordance with this operation dissociation, it has also been demonstrated that adults and even children use a variety of strategies while solving arithmetic operations (Campbell and Timm, 2000;Dehaene and Cohen, 1997;Hecht, 1999;LeFevre et al, 1996;Siegler and Shrager, 1984).…”
Section: Introductionmentioning
confidence: 99%